Internet congestion control - Varma, Subir (Morgan Kaufmann Elsevier, 2015)
The book should enable the reader to gain a good understanding of the application of congestion control theory to a number of application domains such as Data Center Networks, Video Streaming, High Speed Links and Broadband Wireless Networks. When seen through the lens of analytical modeling, there are a number of common threads that run through the design and analysis of congestion control protocols in all these different areas, which are emphasized in this book